1991
DOI: 10.1016/0270-9139(91)90177-w
|View full text |Cite
|
Sign up to set email alerts
|

Export of intracellular HBsAg in chronic hepatitis B virus infection is related to viral replication

Abstract: Serum and liver HBsAg bear an inverse relation to each other during the evolution of chronic hepatitis B virus infection and the quantity of HBsAg in tissue rises gradually with time. In this study, intracellular and extracellular levels of HBsAg were measured by radioimmunoassay in primary culture of hepatocytes from 30 patients with chronic hepatitis B virus infection to determine a possible relationship with hepatitis B virus replication. Serum levels of HBsAg correlated with markers of active viral replica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 8 publications
2
19
0
Order By: Relevance
“…Cells were then counted and resuspended at a concentration of 200,000 cells in 3 ml of medium in Falcon tubes (Becton Dickinson & Co., Rutherford, NJ) and cultured in suspension in the absence or presence of 1 and 10 U/ml of recombinant human IFNy (kind gift of Dr. M. Page, Wellcome Research Laboratory, Beckenham, UK) in a humidified incubator at 37" C for 18 hr. Evaluation by phase-contrast microscopy demonstrated that the isolated hepatocytes prepared using this method retain structural integrity with an intact plasma membrane (14,151. Hepatocyte viability after 18-hr culture also exceeded 80% (range = 82% to 91%) with or without IFNy as assessed by trypan blue dye exclusion and plastic adherence.…”
Section: Hepatologymentioning
confidence: 99%
See 4 more Smart Citations
“…Cells were then counted and resuspended at a concentration of 200,000 cells in 3 ml of medium in Falcon tubes (Becton Dickinson & Co., Rutherford, NJ) and cultured in suspension in the absence or presence of 1 and 10 U/ml of recombinant human IFNy (kind gift of Dr. M. Page, Wellcome Research Laboratory, Beckenham, UK) in a humidified incubator at 37" C for 18 hr. Evaluation by phase-contrast microscopy demonstrated that the isolated hepatocytes prepared using this method retain structural integrity with an intact plasma membrane (14,151. Hepatocyte viability after 18-hr culture also exceeded 80% (range = 82% to 91%) with or without IFNy as assessed by trypan blue dye exclusion and plastic adherence.…”
Section: Hepatologymentioning
confidence: 99%
“…Primary Hepatocyte Culture. The hepatocyte isolation procedure was that described by Trevisan et al (13) with minor modifications (14). The medium used was HEPES-buffered RPMI 1640 media (Gibco Europe, Uxbridge, UK) supplemented with antibiotics (penicillin 200 U/ml, streptomycin 100 kg/ml) and 10% heat-inactivated FBS (Gibco) (pH 7.4, complete medium).…”
Section: Patients (mentioning
confidence: 99%
See 3 more Smart Citations